The Function of Common Sense as a Hegemonic Instrument in Paul Beatty's Novel the Sellout - Abadi, Diana Salsabila; Darmawan, Ruly Indra (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to investigate how deeply ingrained common sense can become as a hegemonic tool of the dominant group, normalizing and naturalizing ideas to the point where they feel like accepted and indisputable realities that can guide actions and thoughts, while also influencing social interactions and identity formation of subaltern groups. This study uses qualitative and descriptive analysis methodologies within the theoretical framework of Antonio Gramsci's theory of hegemony, it is centered on the novel The Sellout by African-American author Paul Beatty that focuses on the interactions and characters in the novel to see how common sense acts as a hegemonic tool that upholds the beliefs, values, and viewpoints of dominant groups. The researcher discovered around forty-two instances of the concept of